Students’ Attitudes and Perceptions of ICT: Weblog Application in Improving Methods of SCL on Writing Class 2: Online Exploration of Global Issues - Marleiny Radjuni (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
In this digitized era, English as a Foreign Languag (EFL) teachers in Indonesia, as in many other countries are anxious to exploit the potential of Information and Communication Technology (ICT) to enhance the teaching and learning process. Given the increasing pressure exerted by technological developments on language education, it is important to understand the underlying factors behind teachers’ decisions regarding ICT. Regarding this matter, this study investigates the development as well as the effects of ICT applied in English Department in teaching and learning process. The use of weblog is being applied in the Academic Writing classes for a couple of years now. Students are equipped with the method of teaching through blog. So far, the use of ICT in the classroom often part of a teacher-centered class but it is easy to exploit these tools in learner-centered activities. For this particular case, students have freedom to control themselves in using the internet technology, even though it is still under teachers instructions. The method applied in this study is combination of the qualitative and quantitative. Evidence has been collected through a literature search, students questionnaires and semi interviews designed. The factors which was found to be most importans to these students were; having the lesson more interesting, easier, more fun for them, more diverse, more enjoyable and on top of that is more motivating.